Modification Monitoring of Combustion Chamber Temperature and Pressure on Diesel Engines - Juna, Haidir; Nufus, Tatun Hayatun; Maksum, Ahmad (Universitas Negeri Semarang, 2021)
Along with the development of technology in the industry, especially automotive, professional workers who are reliable and master their fields in theory and practice are expected. Ideally, educational institutions such as polytechnics should provide adequate equipment and facilities to achieve learning objectives. A critical process in the combustion engine system is where a cycle of pressure and temperature changes at each piston stroke. Unfortunately, many students' understanding of the diesel engine cycle system still needs to be improved, even though the diesel engine cycle had been discussed in the engine system course or thermodynamics. Therefore, this study was intended to modify the Diesel Engine in the heavy equipment workshop to be used as a learning media for the combustion engine and thermodynamic, especially the diesel cycle. This research started with identifying and preparing to identify and to prepare equipment and materials, installing pressure and temperature sensors, controller installation, calibration, and final testing. The test results show the correspondence between the theoretical and experimental cycles, although a few typical differences usually occur between theoretical and practical in the field.